Counting by 7s - Sloan, Holly Goldberg (London Piccadilly Press, 2014)
COUNTING BY 7S tells the story of Willow Chance, a twelve-year-old genius who is obsessed with diagnosing medical conditions and finds comfort in counting by 7s. It has never been easy for her to connect with anyone other than her adoptive parents, but that hasn't kept her from leading a quietly happy life . . . until now. Suddenly Willow's world is tragically changed when her parents both die in a car crash, leaving her alone in a baffling world. Her journey to find a fascinatingly diverse and fully believable surrogate family is a joy and a revelation to read.